Acute kidney injury in Colombian patients with COVID-19 who received kidney support therapy with genius® 90 technology - Rey-Vela, Emilio; Muñoz, Jesús; Rico-Fontalvo, Jorge; Daza-Arnedo, Rodrigo; Portela-Buelvas, Katherin; Pájaro-Galvis, Nehomar; Leal-Martínez, Víctor; Abuabara-Franco, Emilio; Cabrales-Juan, José; Marín, Leonardo; Daza, Lucas; Cuadro, Samuel; et al. (Journal of Clinical Nephrology, 2020)
Introduction: Acute kidney injury (AKI) is one of the complications associated with severe COVID-19 infection, and it can present in up to 20% to 40% of the cases; of these, approximately 20% will require renal replacement therapy (RRT). Objective: To establish clinical and laboratory characteristics in a group of patients from Colombia with COVID-19 infection and AKI that received intermittent and prolonged RRT with the GENIUS® 90 technology in between March and July 2020. Design: Cross-sectional study. Results: 78.9% of participants were men and 21.1% were women. The main comorbidities were the following: Hypertension (65.3%), diabetes mellitus (38.9%), obesity (26.3%), cancer (5.3%), Chronic obstructive pulmonary disease (11.6%), cardiovascular disease (23.2%), active smoking (11.6%). 33.7% had chronic kidney disease (CKD) in the average serum creatinine on admission was 4.4 mg/dl. The following inflammatory markers were elevated: C-reactive protein (CRP), d-dimer and ferritin (20.3 mg/dl, 931 mcg/l and 1174 ng/ml, respectively). 63.5% of patients underwent sustained low-efficiency dialysis (SLED) (6 to 12 hours) and the rest of the patients (36.35%) underwent conventional hemodialysis (less than 4 hours). The mortality of the total patient sample was 36.9%, lower in patients with CKD than in patients with no previous renal disease history (18.7% and 40.1%, respectively). Conclusion: Renal complications are frequent in patients with severe COVID-19. The development of AKI could be an isolated prognostic marker associated with an increase in mortality in patients with COVID-19, and one of the options is intermittent and prolonged RRT with the GENIUS® 90 system.